ROLE OF HYPERTENSION, CARDIOVASCULAR DISEASE AND CARDIOVASCULAR RISK FACTORS ON OUTCOME IN HOSPITALIZED COVID-19 PATIENTS. (April 2021) - Chiarini, Giulia; Boari, Gianluca E.M.; Bonetti, Silvia; Orlandini, Federico Braglia; Malerba, Paolo; Bianco, Gianluca; Faustini, Cristina; Rizzoni, Damiano
Abstract : Objective: Emerging data show that hypertension as well as other cardiovascular risk factors may have a major role on outcome in terms of death on patients with COVID-19. We analysed a population of 258 consecutive patients admitted to General Medicine ward of the Hospital of Montichiari (Brixia, Italy) from 29 February to 30 April 2020. Design and method: A group of 258 consecutive patients (173 males and 85 females, aged 71 ± 14) was enrolled. In 168 patients, high-flow oxygen was required (Venturi mask), 20 patients needed orotracheal intubation and 11 were given continuous positive pressure oxygen therapy (CPAP). Patients were treated with the best approach according to available evidence during pandemic period: anti-malaria agents, anti-viral drugs, antibiotics (azithromycin and others), tocilizumab and low molecular weight heparin (LMWH). As of June 10th, 65 deaths had been observed. Survival curves were calculated according to Kaplan-Meier method. Comparison between groups was performed with Breslow and Mantel-Cox test. Results: As shown in the table, a significant raise in mortality was observed in patients older than 65 years (p < 0.001), of male sex (p < 0.001), hypertensives (p < 0.001) as well as in patients with heart disease (picture 1; p < 0.001), COPD (picture 2; p = 0.004), diabetes (p < 0.001) and neoplasms (p = 0.03) compared with patients with no comorbidities or different diseases, both at discharge and at standard follow-up. The number of comorbidities impacted on survival as well. Figure. No caption available. Conclusions: Hypertension, heart disease and cardiovascular risk factors play a significant role as a negative prognostic factor in patients affected by SARS-CoV-2 pneumonia. This confirms previous observations (Pol Arch Intern Med 2020;130(4):304–309) and outlines the importance of prevention of contagion in population with cardiovascular risk factors or established cardiovascular disease.